Proyecto de alcantarillado en la isla "Las casitas" Archipiélago de Jambelí, provincia de El Oro - Moreno Albán, Luis Bladimir (2013)
One of the most relevant problems is the lack of basic services such as the Sanitary Sewer network, so the construction of this would prevent the collapse of the Septic Tanks, which would significantly reduce the contamination of groundwater, preventing the population from contracting diseases. , and thus improve the standard of living of the Community. The Sewer System will necessarily have a Wastewater Treatment Plant; in order to cause the least impact to the ecosystem since it is very sensitive for its particular characteristics.